IMPACT OF COAL MINING IN FOREST AREA TO CARBON EMISSION IN KUTAI KARTANEGARA, EAST KALIMANTAN - Kartikasari, Retna; Rachmansyah, Arief; Leksono, Amin Setyo (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
Coal mining is an activity that contribute to greenhouse gas emissions, both from methane gas release of coal trap and the loss of lan cover plants. This study was conducted to estimate carbon emissions in coal mining areas inside forest areas by analyzing changes in landcover. The area of this study is Kutai Kartanegara Regency, East Kalimantan, where coal mining activities are quite massive. To obtain the extent of changes in land cover and the amount of carbon emissions in the area, analysis of Landsat 5 TM and Landsat 7 ETM+ imagery in 2010 and also the 2016 Landsat 8 OLI / TIRS imagery was used. The results showed that in the area of study there was a change in landcover of 12,663.28 Ha in the forest areas used for coal mining activities. Carbon emissions generated from this activity amounted to 0.60 Mton CO2-Eq